The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11307-015-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution Study of Intravenously Injected Cetuximab-IRDye700DX in Cynomolgus Macaques

Abstract: Both IR700 and intact cetuximab-IR700 biodistributions were consistent with known epidermal growth factor receptor (EGFR) expression, and changes between 2 and 14 days were consistent with rapid metabolism and excretion of the cetuximab-IR700.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Although we did not evaluate ZIKV-specific antibody levels in lymph nodes in the present study, studies with monoclonal antibodies have shown substantial variation in antibody biodistribution to different tissues, including lymph node and brain, as compared with peripheral blood (de Boer et al, 2016; Tichauer et al, 2014; Wang et al, 2008). In the CSF, it is likely that the absence of ZIKV-specific antibodies contributed to viral persistence in that compartment.…”
Section: Discussionmentioning
confidence: 95%
“…Although we did not evaluate ZIKV-specific antibody levels in lymph nodes in the present study, studies with monoclonal antibodies have shown substantial variation in antibody biodistribution to different tissues, including lymph node and brain, as compared with peripheral blood (de Boer et al, 2016; Tichauer et al, 2014; Wang et al, 2008). In the CSF, it is likely that the absence of ZIKV-specific antibodies contributed to viral persistence in that compartment.…”
Section: Discussionmentioning
confidence: 95%
“…However, in general, very few details are given on the development and formulation of these tracers (14,24,(33)(34)(35). Several publications have addressed the translation and clinical implications of NIR imaging, but these discuss mostly the camera technology and the design of clinical trials (31,32,36,37), leaving researchers with little guidance on the steps required to progress a tracer from experiment to clinical product.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lymph node and cancer physiology, rather than cancer‐specific binding, can dominate the pharmacokinetics of imaging agents in terms of their accumulation and retention in lymph nodes for both systemically and locally delivered methods. To account for this, a growing number of groups have been using so‐called paired‐agent or ratiometric imaging methods.…”
Section: Molecular Targeted Imaging Agent Methodsmentioning
confidence: 99%
“…A common concern regarding the clinical translation of paired‐agent imaging protocols is that it is already very onerous to approve 1 imaging agent for clinical use, let alone 2. With respect to this, there are recent unpublished results in our lab suggesting that indocyanine green—which is already approved for clinical use and has now been used in multiple lymph node mapping applications—can act as an ideal control imaging agent when coadministered with IRDye700DX‐labeled antibodies, such as the GMP‐produced, and ready‐for‐human‐use, anti‐EGFR agent developed by de Boer et al…”
Section: Paired‐agent and Ratiometric Methodsmentioning
confidence: 99%